A History of the Introduction and Shut Down of Therac-25 - Anonymous (Online Ethics Center, 2020)
The case history is an overview of the case from the design of Therac-25 to the eventual shut-down of the machine pending redesign. It serves as a short history and guide to the case to give you your bearings.
Case Study / Scenario|Educational Activity Description|Historical / Non-Fiction Case
Keywords: Catastrophes; Hazards; Disasters; Ethics and Society; Product Liability; Research and Practice; Safety